Entrepreneurship in China - Han, Jimmy Jam Kwan (2015)
The successful conclusion of the NAFTA treaty has spelt a new world order for free trade and economic growth. China is poised to become an important superpower in the area of economic competition in the coming decade. The potential for further economic development in China is vast. In the past five to ten years, there has been a growing emphasis of countries to trade and set up businesses in China. The opportunities are abundant. In particular, Singapore has been stepping up its ties and relations with mainland China. Unfortunately, investment in China is plagued with many uncertainties that make the business investment potentially problematic. One of these uncertainties can be seen in its fledgeling legal system which seems to be based on guanxi instead of proper legal proceedings. Also, the economic situation is highly unstable, as can be seen in its spiralling inflation and the recent currency floatation measures. Therefore, the purpose of this report is to provide some suggestions and recommendations on how these entrepreneurs can establish and conduct their businesses in China in view of the uncertainties and problems that they face. These ideas are built from in-depth interviews with five managing directors and literature reviews from many established journals. In this report, we shall first be looking into the institutional pillars of China. The political, social, cultural, economic and legal aspects of the country will be examined. This is to provide a launching pad from which our report will progress. We shall also be analysing case studies of both Hong Kong and Singapore entrepreneurs. In the analysis of these case studies, we have come up with various entrepreneurial qualities present in businessmen operating in China. It seems that successful entrepreneurship can be seen in four categories of skills. They are personal, interpersonal, technical and conceptual skills. After contrasting local entrepreneurs with the preferred entrepreneurial qualities, our group has discovered that an "entrepreneurial vacuum" exists among the local entrepreneurs. The gaps that are found include Singaporeans being too pampered; the predominance of the "kiasi" spirit and the tendency of Singaporeans being more like managers than entrepreneurs. Other gaps are the lack of top connection with the Chinese government as well as the lack of ''born there" advantage and information. Recommendations for further improvements are also discussed. These include the government's continuous efforts to promote entrepreneurship; fostering creativity through changing the education system; and providing support for Singapore expatriates in China. In addition, the government should provide up-to-date and accurate information, nurture top level ties with Chinese officials, aid China in charitable deeds and improve the learning of Mandarin. Furthermore, there should be more cultural and academic exchange programmes and greater appreciation of Chinese management practices. Finally, topics for further research are suggested. One such topic hopes to investigate whether "Chinese-oriented" entrepreneurs would do better in China than those who are more "Westernised" in their outlook. The other topic seeks to test the relationship between a nation's social security and the thriving of the entrepreneurial spirit.